The Tragedy Of Hamlet, Prince Of Denmark - Shakespeare, William; Barbara A Mowat; Paul Werstine (Newyork Simon And Schuster Paperbacks, 2012)
Hamlet Summary. The ghost of the King of Denmark tells his son Hamlet to avenge his murder by killing the new king, Hamlet's uncle. Hamlet feigns madness, contemplates life and death, and seeks revenge. His uncle, fearing for his life, also devises plots to kill Hamlet.
Includes detailed explanatory notes
Keywords: English Drama -- Denmark-Drama -- Kings and Rulers-Drama -- Revenge-Murder Victims Families-Drama